2023
DOI: 10.1111/cts.13519
|View full text |Cite
|
Sign up to set email alerts
|

Clinical development time is shorter for new anticancer drugs approved via accelerated approval in the US or via conditional approval in the EU

Abstract: The US Food and Drug Administration (FDA) and the European Medicines Agency (EMA) offer expedited regulatory approval programs for drugs with high potential patient value applicable at different stages leading to marketing authorization: (i) drug development (fast track designation (FTD), breakthrough therapy designation (BTD), regenerative medicine advanced therapy designation in the United States, and priority medicines scheme in the European Union), (ii) review of marketing authorization application (priori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…In addition, not specific to but applicable also for orphan-designated drugs, expedited regulatory programs as offered by the FDA and the European Medicines Agency (EMA), in the US and the EU, respectively, support the development of drugs (e.g., breakthrough therapy designation (BTD) and fast track designation (FTD) in the US, and priority medicines scheme (PRIME) in the EU), provide shorter marketing application review times (e.g., priority review designation in the US, and accelerated assessment in the EU) or provide preliminary approval (e.g., accelerated approval in the US, and exceptional circumstances and conditional marketing authorization in the EU) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, not specific to but applicable also for orphan-designated drugs, expedited regulatory programs as offered by the FDA and the European Medicines Agency (EMA), in the US and the EU, respectively, support the development of drugs (e.g., breakthrough therapy designation (BTD) and fast track designation (FTD) in the US, and priority medicines scheme (PRIME) in the EU), provide shorter marketing application review times (e.g., priority review designation in the US, and accelerated assessment in the EU) or provide preliminary approval (e.g., accelerated approval in the US, and exceptional circumstances and conditional marketing authorization in the EU) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Demirci et al. 5 evaluated the clinical development time for 76 new anticancer drugs, using the earliest clinical trial start date to the date of submission of the marketing authorization application (MAA) in the United States. The study revealed how utilizing combinations of expedited regulatory approval programs is associated with shorter clinical development times, potentially benefiting the pharmaceutical industry by allowing earlier drug availability.…”
mentioning
confidence: 99%